The inverse of a function, say, #f(x)#, is a function #f^-1(x)# such that #f^-1(f(x)) = x#. To obtain the inverse function, manipulate the equation so that #x# is isolated on one side.
Function 1: #f(x) = -(x)/(12)#
We could multiply each side by #-12#:
#-12f(x) = x#
So, it must be that #f^-1(x) = -12x#. Let's test it to be sure:
#f^-1(f(x)) = -12(f(x)) = -12(-(x)/(12)) = x#.
Alright!
Function 2: #f(x) = (x - 12)/4#
Multiply each side by #4#:
#4f(x) = x - 12#
Add each side by #12#:
#4f(x) + 12 = x#
So #f^-1(x) = 4x + 12#.
#f^-1(f(x)) = 4(f(x)) + 12 = 4((x - 12)/4) + 12#
#= x - 12 + 12 = x#.
Function 3: #f(x) = (3x + 1)/6#
Multiply each side by #6#:
#6f(x) = 3x + 1#
Subtract #1# from each side:
#6f(x) - 1 = 3x#
Divide each side by #3#:
#6/3 f(x) - 1/3 = x#
#2f(x) - 1/3 = x#
So #f^-1(x) = 2x - 1/3#.
#f^-1(f(x)) = 2(f(x)) - 1/3 = 2((3x + 1)/6) - 1/3#
#= (3x + 1)/3 - 1/3 = (3x)/3 = x#.